Establishment of an entrepreneurial studio as a forum for increasing student entrepreneurship interest - Muhammad Syaiful; Hariono Hariono; Meilan Anjasari (Community Empowerment, 2022)
Entrepreneurship courses are offered in almost all university majors and study programs. This is a pledge to assist the government in its efforts to minimize the number of unemployed. However, the factual conditions discovered a number of issues, including students' lack of entrepreneurial interest, the lack of a product marketing forum, and inadequate facilities and infrastructure. The aim of this program is to create an entrepreneurial studio that will serve as a venue for students to learn more about entrepreneurship. Preparation for the establishment of a studio and soft launching, as well as an entrepreneurial inspiring speaking (BISA) webinar, are the methods employed in this service. According to participant testimonies, this activity resulted in the creation of an entrepreneurial studio as a forum for students entrepreneurship, as well as an increase in students' interest in entrepreneurship after participating in the Entrepreneurship Inspirational Talk (BISA).